The reasons of the implementation of the concept of smart villages in the European Union - Panciszko, Barbara (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2021)
The aim of this article is to identify the main challenges facing the rural areas in the European Union (EU) and to investigate whether implementation of the concept of smart villages makes it possible to face these challenges. These challenges are: depopulation, aging of the society, climate change, growing demand for food, environmental degradation, peripheralization or low income of rural populations, pandemic COVID-19. The first part describes the situation in rural areas, using statistical data from the reports of the European Commission and Eurostat. Then the roots of the concept of smart villages in the European Union were presented. Its six components have been identified: smart society, smart economy, smart agriculture, smart management, smart environment and smart associability. In the last part, it was checked whether the implementation of the concept of smart villages responds to the main challenges faced by rural areas.

Celem niniejszego artykułu była identyfikacja głównych wyzwań stojących przed obszarami wiejskimi w Unii Europejskiej (UE) oraz zbadanie, czy realizacja koncepcji smart villages umożliwi sprostanie tym wyzwaniom. Do tych wyzwań zaliczamy: depopulację, starzenie się społeczeństwa, zmiany klimatyczne, rosnący popyt na żywność, degradacja środowiska, peryferyzacja, czy niskie dochody populacji wiejskich oraz pandemię COVID-19. W pierwszej części dokonano charakterystyki sytuacji na obszarach wiejskich, wykorzystując dane statystyczne pochodzące m.in. z raportów KE i Eurostatu. Następnie zaprezentowano korzenie koncepcji smart villages w Unii Europejskiej. Wyszczególniono sześć jej komponentów: smart society, smart economy, smart agriculture, smart management, smart environment and smart associability. W ostatniej części sprawdzono, czy wdrożenie koncepcji smart village odpowiada na główne wyzwania stojące przed obszarami wiejskimi.
Uwarunkowania wdrażania koncepcji smart villages w Unii Europejskiej
Keywords: smart villages; European Union; rural areas; smart accessibility; smart environment; smart rural society; smart villages; Unia Europejska; obszary wiejskie; smart dostępność; smart środowisko; inteligentne społeczności wiejskie